Synergistic dominance induced by hip extension exercise alters biomechanics and muscular activity during sprinting and suggests a potential link to hamstring strain - Iguchi, J.; Hojo, T.; Fujisawa, Y.; Kuzuhara, K.; Yanase, K.; Hirono, T.; Koyama, Y.; Tateuchi, H.; Ichihashi, N. (The Journal of Strength and Conditioning Research, 2023)
Hamstring strain is likely to occur during the late swing phase or the first half of the stance phase in sprinting. During the late swing phase, the hamstrings and gluteus maximus (Gmax) contract eccentrically to decelerate the lower limb. We hypothesized that, when the Gmax becomes dysfunctional because of delayed onset muscle soreness (DOMS), the hamstring workload is increased (i.e., there is synergetic dominance), which could lead to an increased risk of strain. A total of healthy 15 male undergraduate or graduate students (age 23.1 ± 1.28 years) were recruited to perform exercises and maximal sprints. On day 1, before subjects performing DOMS-causing exercises, and on day 3, while subjects were experiencing DOMS in the Gmax, lower-limb biomechanical and muscle activity data were recorded using a motion analysis system and electromyography (EMG), respectively. Data were analyzed and compared between day 1 and day 3. Hip flexion angle on day 3 was significantly lower than that on day 1, but the opposite was true for the knee flexion angle (P < 0.05). Vastus medialis (VM), biceps femoris (BF), and Gmax muscle activities on day 3 were significantly higher than those on day 1 (P < 0.05). Peak propulsive forces on day 3 were significantly higher than those on day 1 (P < 0.05). Kinematic changes such as decreased hip flexion angle and EMG changes such as increased BF EMG activity on day 3 to compensate for the loss of function of the Gmax may potentially increase the risk of hamstring strain.